Damage characteristics and constitutive modeling of coal under real-time temperatures - Yongjiang Yu; Ning Liu; Guoning Zhang; Jiaming Liu; Jijie Wei (PLoS ONE, 2026)
The thermal-mechanical coupling effects induced by thermal injection during coalbed methane extraction can readily lead to coal seam instability. To investigate the influence of real-time temperature on the damage characteristics of coal, uniaxial compression tests were conducted on coal specimens under real-time temperature conditions using the MTS 815 testing system equipped with high-temperature accessories. Combined with the PFC3D discrete element numerical model, a cross-scale analysis was performed to examine the mechanical degradation patterns and fracture evolution characteristics of the coal. Based on a temperature-load coupled damage variable approach, a segmented damage model under combined thermal-mechanical effects was developed. The results show that the peak strain of coal is positively correlated with temperature, whereas compressive strength and elastic modulus exhibit a negative correlation. Thermal damage degree is positively correlated with temperature, with thermal cracks being predominantly tensile. During loading, as temperature increases, the macroscopic failure mode gradually shifts from axial splitting to mixed tensile-shear failure. Microdamage observed in PFC simulations similarly evolves from a predominance of tensile cracks to a mixed pattern, accompanied by a significant increase in the strain range between the initiation point and the peak point, indicating enhanced ductility. To account for the thermal sensitivity and the influence of temperature on failure mechanism, a Gaussian decay function based on a Gaussian kernel function was constructed to reconstruct the post-peak curve of the traditional Weibull model, substantially improving the model’s descriptive capability. The proposed damage constitutive model is applicable to thermomechanically coupled uniaxial compression tests on coal and accurately captures the damage evolution process. The findings provide theoretical support for assessing coal seam stability during thermal injection mining.